2020
DOI: 10.1021/acs.analchem.0c02389
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Aggregated Three-Dimensional Cell Culture Model by Multimodal Mass Spectrometry Imaging

Abstract: Mass spectrometry imaging (MSI) is an established analytical tool capable of defining and understanding complex tissues by determining the spatial distribution of biological molecules. Three-dimensional (3D) cell culture models mimic the pathophysiological environment of in vivo tumors and are rapidly emerging as a valuable research tool. Here, multimodal MSI techniques were employed to characterize a novel aggregated 3D lung adenocarcinoma model, developed by the group to mimic the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 61 publications
2
58
0
Order By: Relevance
“…From the segmentation analysis, differences of the phenotypical regions in each model were observed ( Figure 1 ). As reported previously [ 14 ], the segmented image of an HCC827 aggregoid model comprised three regions: a distinctive inner core, an annular zone and an outer region, which were also observable in the histological image. The segmentation of the MG63 model showed a similar pattern, where a core, two annular regions and a periphery were observable in the segmented MSI data.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…From the segmentation analysis, differences of the phenotypical regions in each model were observed ( Figure 1 ). As reported previously [ 14 ], the segmented image of an HCC827 aggregoid model comprised three regions: a distinctive inner core, an annular zone and an outer region, which were also observable in the histological image. The segmentation of the MG63 model showed a similar pattern, where a core, two annular regions and a periphery were observable in the segmented MSI data.…”
Section: Resultsmentioning
confidence: 53%
“…Furthermore, we have previously employed multimodal MSI techniques to demonstrate how obtaining a large amount of molecular information with a complementary nature can enhance the understanding of the biological processes within a tissue. The detection of metabolites, proteins and metals determined the interplay between molecules and established key pathways that defined a novel HCC827 lung adenocarcinoma ‘aggregoid’ model [ 14 ]. A similar approach could therefore give a valuable insight into 3D tumour aggregoid models of OS, providing comprehensive information of biochemical pathways that influence the cancer pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Imaging mass cytometry (IMC) can provide additional information regarding cellular localization within tissues and can help clarify the spatial interactions between different cell types ( 17 ). In addition, IMC has been used to define the metabolite distribution in a lung adenocarcinoma model ( 18 ) and to determine that cancer-associated fibroblasts interact with monocytic myeloid cells to induce immune suppression in the TIME of patients with LUSC ( 19 ). Therefore, we used IMC to characterize the TIME’s immune atlas in specimens from patients with primary LUSC, which may help clarify the TIME landscape and explore the cancer–immune interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Although, it is an understandable requirement to use more advanced models that can be grown large enough to study the spatial distribution of molecules. For example, a recent study by Flint et al [43] reported the use of multimodal MSI techniques: DESI, imaging mass cytometry (IMC) and laser ablation inductively coupled plasma (LA-ICP)-MS to characterize a novel aggregated 3D culture model of lung adenocarcinoma. The in vitro model, termed 'aggregoid' is formed via the aggregation of clonal tumor spheroids to create a more heterogeneous tissue of approximately 1 mm diameter.…”
Section: Article Highlightsmentioning
confidence: 99%